Feasibility Study of Offshore Wind Wheel Installation in South China Sea at Malaysia - MAT TARMIZI, NURFATIN NASYITAH; ROSLY , NURHAYATI (Progress in Aerospace and Aviation Technology, 2023)
As the global demand for renewable energy continues to rise, it becomes crucial to investigate the viability of offshore wind power generation. This thesis presents a comprehensive feasibility study assessing the viability of the South China Sea wind turbine installation. This study will describe the current situation of wind energy across the world and specifically discusses offshore wind farm technology. The study begins with a comprehensive literature review emphasizing the significance of wind power in mitigating climate change and reducing reliance on fossil fuels. The objectives of this are to study on the availability of offshore wind resources in Malaysia and to analyse the effect of micro-siting towards wind farm energy production and performance. This study indicates the best sites to set up offshore wind farm in Malaysia. According to the data, Mersing has a favorable availability of wind resources, which makes it the best place to put the turbines. Critical review for better understanding about the importance of micro-siting of wind farms social and economic was conducted. The micro-siting technique is helpful since it provides a methodical and well-informed way of choosing a location. It helps decision-makers strike a balance between the project’s, the community’s, and the environment’s demands by considering various elements and tailoring the analysis to the particulars of a certain project. As technology and methodology evolve, the micro-siting approach will become more important in attaining sustainable and efficient development.